2009
DOI: 10.1590/s0004-28032009000300006
|View full text |Cite
|
Sign up to set email alerts
|

Achados colonoscópicos em pessoas sem quadro clínico de doença colorretal

Abstract: RESUMO -Contexto -O câncer colorretal é causa de morte frequente e sua prevenção deve fazer parte dos programas de rastreamento em indivíduos assintomáticos. Objetivo -Avaliar os achados colonoscópicos de pessoas assintomáticas submetidas a colonoscopia. pólipos em 64,28%, doença diverticular em 27,92%, alterações inflamatórias em 9,74%, melanose colônica em 2,6% e angioectasias em 7,8%. Houve incidência maior de pólipos em indivíduos acima de 50 anos. A análise de regressão logística mostrou a idade e sexo co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
2
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 24 publications
4
2
0
2
Order By: Relevance
“…They were primarily located in the ascending colon, transverse colon, and rectum; in the latter, a higher incidence of multiple polyps was observed. 15 This data was very similar to the present findings, where polyps were more commonly observed in the rectum, sigmoid colon, and transverse colon.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…They were primarily located in the ascending colon, transverse colon, and rectum; in the latter, a higher incidence of multiple polyps was observed. 15 This data was very similar to the present findings, where polyps were more commonly observed in the rectum, sigmoid colon, and transverse colon.…”
Section: Discussionsupporting
confidence: 93%
“…In the study by Petroianu, pre-malignant lesions were observed in one-quarter of the patients, demonstrating that the removal of these lesions endoscopically prevents cancer and all its consequences, which can sometimes be fatal, 15 and thus reinforcing the importance of polypectomy, a procedure performed in 70 of the patients in the present study.…”
Section: Discussionsupporting
confidence: 71%
“…A high cell-proliferation index suggests a more aggressive behavior on part of the neoplasm and may have important prognostic implications (22) . The average age of the study population was 63 years and the sex distribution was fairly equal, matching findings in the literature showing the prevalence of polyps in patients aged >50 years, with no sex preference (9,11,18,32) . The data also support the claim that patients with adenomas and colorectal cancer have a similar age distribution (generally >50 years) (1,11,21) .…”
Section: Discussionsupporting
confidence: 84%
“…There was a higher incidence of adenoma and dysplasia in patients over the age of 50, but the difference did not reach statistical significance. Other studies have reported a higher incidence of adenomas in general and advanced adenomas in particular after the fifth decade of life 23 , 18 . There were no significant between-group differences in presence of villous component.…”
Section: Discussionmentioning
confidence: 85%